Molecular incidence of Toxoplasma gondii, Neospora caninum, and Cryptosporidium parvum in dissimilar kinds of raw and pasteurized milk samples of naturally infected animal species - Abdollahzadeh, Farzad; Firouzabadi, Mohammad Sadegh Safaee; Shomali, Romina Rashid (Penerbit Universiti Kebangsaan Malaysia, 2022)
Milk of naturally infected animal species is considered an essential reservoir of Toxoplasma gondii, Neospora caninum, and Cryptosporidium parvum. An extant survey was performed to measure the T. gondii, N. caninum, and C. parvum incidence and periodic frequency amongst milk samples. One-thousand and one-hundred and sixty raw and 400 pasteurized milk samples were collected. Milk samples were used for DNA extraction. The nested-polymerase chain reaction was applied to diagnose B1, NP, and hsp70 genes of the T. gondii, N. caninum, and C. parvum, respectively. The total incidence of T. gondii, N. caninum, and C. parvum in examined milk samples were 2.69%, 10.51%, and 2.94%, respectively. Co-contamination of examined milk samples with all three protozoa was 0.38%. T. gondii had the highest distribution amongst raw sheep (5.00%) milk samples, while N. caninum, and C. parvum had the highest distribution in raw buffalo (23.68% and 6.31%, respectively) milk samples. Marked periodicity with the higher distribution of all protozoa among raw milk samples collected during autumn and summer seasons were found (P <0.05). Raw milk of animal species and pasteurized cow milk may be reservoirs of N. caninum, T. gondii, and C. parvum. Accurate monitoring of raw and pasteurized milk, particularly in autumn and summer seasons, can diminish the risk of human and animal toxoplasmosis, cryptosporidiosis, and neosporosis. However, further investigations are essential to understand the exact epidemiological aspects and other risk factors associated with the N. caninum, C. parvum, and T. gondii presence in raw and pasteurized milk.